Salt Tolerance of Several Aquatic Plants - Izzati, Munifatul (Proceeding International Conference on Global Resource Conservation, 2015)
Aquatic plant has an important role in aquaculture management.Â We interested in studying their salt tolerance to give guidance in choosing the right species for better management. In preliminary study we test 20 species to test their survival on different level of salinity. Collected sample were washed, weighed and placed in 100 L of different level salinity of water (5 ppt, 10 ppt, 15 ppt, 20 ppt, 25 ppt and 30 ppt). Their survival was indicated by their color and freshness of remaining biomass. Their growth rate in different salinity level was also studied for only three species, Hydrilla verticillata, Ceratophyllum demersum and Salvinia molesta, as these three species were the most tolerant to salinity change. Measurement of their growth respond to salinity change, was done by growing plant biomass in fresh water, and then gradually added with salt to increase water salinity to level of 2 ppt each week. Â Results indicated that, Pistia stratiotes and Lemna minor are most tolerant to salinity. This two aquatic plant species were survives in range of salinity from 5 ppt to 15 ppt. Chaetomorpha is the most tolerant to salinity range from 0 ppt to 20 ppt. From marine alga, Gracilaria verrucosa is the most tolerant to salinity of 10 ppt to 35 ppt. In studying the growth rate, Hydrilla verticillata give the best performance in adaptation to salinity change. The species that has better adaptation to salinity change will be to be used in aquaculture management. It is recommended that, in close to fresh water, Hydrilla and Pistia will give the best candidate for aquaculture management. Chaetomorpha the best for either fresh or brackish water, while Gracilaria is recommended to be used for aquaculture management in water close to high salinity to moderate one.Keywords: Aquatic plant; Gracilaria; Hydrilla; Lemna; salt; tolerance